Negotiating uncertainty in UK-EU relations: Past, present, and future - David Henig (European Centre for International Political Economy (ECIPE), 2024)
Europe has been weakened by dif̈Icult UK-EU relations at a time of international challenge. Eight years after the Brexit referendum a new UK government and European Commission provides a good opportunity to reset approaches and put obstructions aside. Too big for either side to ignore, this will always be an important, time-consuming, and slightly chaotic relationship - which thus needs a much firmer footing based on the following shared understanding:
Keywords: 330; Internationale Wirtschaftsbeziehungen; Großbritannien; EU-Staaten